Discourse patterns of affective stance in paediatric online consultative encounters - Opeyemi Olajimbiti Ezekiel; Ayoola Samuel Olayiwola (Language and Semiotic Studies)
The paediatric online consultative forum, where putative patients interact with physicians, has become a lifesaver for many, especially during the COVID-19 lockdown era in Nigeria. Examining the affective stance expressed by mothers in this asynchronous discourse from the linguistic perspective adds to the few existing studies on telemedicine and reveals the plight of mothers and their children in Nigeria. This study examines the discourse patterns of affective stance and its linguistic markers in online consultative encounters. Using the purposive random sampling method, 80 posts on the Facebook account “Ask the Paediatricians” between May and June 2020 and analysed using stance theory. Findings show that mothers express affectivity as interrogative, attention and hypothetical markers to project their concerns, worries, and curiosity about their children’s health status, e.g., breastfeeding, immunization, stools abnormalities, nutrition, fever, refluxing babies among others. Self-mentions and attitude markers are the two linguistic markers predominantly deployed in expressing affective stance. While the instances of self-mentions index affective representation, attitude markers, on the other hand, foreground affective attitude toward the propositions expressed. The above implies the level of emotional conditions of motherhood and sociocultural experiences of Nigerian women in the context of telemedicine encounters in child health studies.